Psychological and Pedagogical Features of Teaching Students to Critically Evaluate the Personality of the Characters in Literature Classes - Roza Khasanovna, Niyazmetova; Ikbal Tadjibaevna, Baltaeva; Anadjan Tadjibaevna, Baltaeva (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the problem of shaping students’ critical evaluation skills, which evaluate literary heroes in literary works. The article reveals the features of the development of students’ critical thinking in the process of studying literary work and emphasizes the technology of the formation of skills of critical evaluation of literary work. Effective technical methods are methods that help to develop creative activity, analyze, observe, compare, generalize, and other skills.